Staphylococcus aureus Internalized by Skin Keratinocytes Evade Antibiotic Killing - Al Kindi, Arwa; Alkahtani, Abdullah M.; Nalubega, Mayimuna; El-Chami, Cecile; O’Neill, Catherine; Arkwright, Peter D.; Pennock, Joanne L. (Frontiers in Microbiology, 2019)
Staphylococcus aureus causes the majority of skin and soft tissue infections. Half of patients treated for primary skin infections suffer recurrences within six months despite appropriate antibiotic sensitivities and infection control measures. We investigated whether S. aureus internalized by human skin keratinocytes are effectively eradicated by standard anti-staphylococcal antibiotics. S. aureus, but not S. epidermidis, were internalized and survive within keratinocytes without inducing cytotoxicity or releasing the IL-33 danger signal. Except for rifampicin, anti-staphylococcal antibiotics in regular clinical use, including flucloxacillin, teicoplanin, clindamycin and linezolid, did not kill internalized S. aureus, even at 20-fold their standard minimal inhibitory concentration. We conclude that internalization of S. aureus by human skin keratinocytes allows the bacteria to evade killing by most anti-staphylococcal antibiotics. Antimicrobial strategies, including antibiotic combinations better able to penetrate into mammalian cells are required if intracellular S. aureus are to be effectively eradicated and recurrent infections prevented.